FRI0411 Response and drug survival of sulfasalazine in an observational study (nor-dmard) of dmard-naïve patients with axial spondyloarthritis (SPA). (23rd January 2014) - Fagerli, K. M.; van der Heijde, D.; Heiberg, M. S.; Wierød, A.; Rødevand, E.; Mikkelsen, K.; Kalstad, S.; Kvien, T. K.; Lie, E.
Abstract : Background: Current recommendations for the treatment of ankylosing spondylitis (AS) states that sulfasalazine (SSZ) may be used for patients who have peripheral disease as there is some evidence of efficacy (1). However, SSZ is not recommended for patients with only axial disease, as there was no proof of efficacy in this group (1). Objectives: Investigate the response and drug survival of SSZ in patients with axial SpA, and especially compare outcomes in patients with and without swollen joints. Methods: Data is from NOR-DMARD, a Norwegian, multi-centre longitudinal observational study of DMARD treatment in inflammatory joints diseases. Patients had a clinical diagnosis of axial SpA (ICD-10: M45, M46.1, M46.8 and M46.9) and started SSZ as their first DMARD were included in the current analyses. Response was assessed by patient global assessment, physician global assessment, MHAQ, SF-6D, CRP, number of swollen joints, and ASDAS, BASDAI and ASAS responses. As BASDAI was only included in the data collection in 2006, ASDAS, BASDAI and ASAS responses were not available for all patients. Groups were compared using independent t-test, chi-square, Fisher exact test and Mann-Whitney U-test as appropriate. Results: We included 181 DMARD-naïve SpA-patients who were starting treatment with SSZ. Baseline characteristics were (mean (SD) unless stated otherwise): Age 40.4 (11.9) yrs, 54.1% males, 83.8% HLA-B27 positive, disease duration median (IQR) 2.6 (0.1-11.1) yrs, 52.2% with swollen joints, ASDAS 3.1 (0.9), BASDAI 5.2(2.0), patient global 53.4 (20.8). Patients with swollen joints at baseline were somewhat older and had higher baseline CRP and ASDAS. 3-month responses were available for 139 patients, and are shown in the table . Analyses corrected for baseline differences yielded similar results. Three-year drug survival was statistically significantly better in patients with swollen joints (0.10 vs. 0.22 (p=0.03)). Conclusions: Overall, responses to SSZ were modest in this population of DMARD-naïve axial SpA-patients. There was a trend towards a slightly better 3-month response and significantly better 3-year drug survival in patients with peripheral joint swelling, supporting the recommendation of SSZ in this patient group. References: Braun J et al. Ann Rheum Dis 2011;70:896–904. Disclosure of Interest: None Declared